ESG Disclosure in the Sustainability Reports of Indonesian Banks 2022 - Prihandini, Wiwiek (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The increasing global emphasis on Environmental, Social, and Governance (ESG) principles has led to heightened expectations for corporate transparency and accountability, particularly in the banking sector. ESG disclosure in sustainability reports serves as a key instrument in ensuring that banks integrate sustainable finance practices into their operational and investment strategies. However, variations in ESG rating methodologies and reporting frameworks present challenges in assessing the credibility and comprehensiveness of ESG disclosures. This study examines the extent of ESG disclosure in the sustainability reports of Indonesian banks, comparing the practices of state-owned and private banks. Using content analysis, this research evaluates ESG disclosures based on 31 indicators derived from the International Finance Corporation (IFC) ESG Framework. The findings indicate that while some banks provide structured ESG disclosures, many still lack depth and quantitative detail, with key environmental and governance aspects often underreported. The results also highlight a correlation between ESG disclosure and bank size, where larger banks tend to have more structured and transparent sustainability reports. Additionally, ESG disclosure levels in sustainability reports are found to align with bank rankings in the IDX ESG Leader Index, suggesting a potential relationship between voluntary disclosure practices and external ESG assessments. This study contributes to the ongoing discourse on ESG reporting standards by advocating for more standardized, comprehensive, and globally aligned ESG disclosures in the Indonesian banking sector. The research provides recommendations for regulators, investors, and banks to enhance ESG transparency, reduce greenwashing risks, and strengthen the credibility of sustainability reports. Keywords: ESG Disclosure, Sustainability Reports, Banking Sector, IFC ESG Framework, IDX ESG Leader, Content Analysis